Extending the market: increasing sustainability potential through public transit in Lee’s Summit - Workmon, Mitchell R. (Kansas State University, 2012)
Investigating historical trends of public transportation, two distinct groups of riders are targeted. First, individuals living and working in large metropolitan centers, and second, people who are dependent upon public transit; referring to people who cannot afford personal automobile transportation, possess no driver’s license, or are physically unable to drive (Garrett and Taylor, 1999). Analyzing the national demographics related to age and poverty levels, transit dependents make up only approximately 25% of the United States population. Expanding transit ridership will make our nation’s transportation sector more sustainable. Public transportation systems yield exceptional benefits including economic and community vitality, gasoline consumption reduction, air quality improvement and diverse cultural interactions promoting social cohesion (Metro Transit- St. Louis, 2010). This report focuses on ridership potential in the Rock Island Corridor, an unused rail thoroughfare in Kansas City. Local governing organizations are analyzing the corridor for future commuter rail implementation. In order to attain higher ridership and ensure long-term viability, the commuter rail must attract residents that are not dependent upon public transportation. This project maps transit dependencies along the Rock Island Corridor looking at income levels, home values, and commuting distance. The findings illustrate that Lee’s Summit is not dependent upon public transit and has tremendous potential to impact the ridership and development direction along the corridor. Looking into the future of the corridor the time to plan is now. Lee’s Summit is expected to see a population increase of 40,636 people (a 50% increase) by the year 2040 (Mid-America Regional Council, 2010). The strategies applied to Lee’s Summit are applicable to other similar suburbs of Kansas City, ultimately making Lee’s Summit a catalyst for the region. The organization of the project is focused around three major sections. The first section explores and analyzes current public transit practice in terms of ridership and aesthetics. The second section explains a three-part strategy focused around a park-n-ride and a transit-oriented development, both supported by a municipal feeder bus system. The third section demonstrates design and program ideas for the park-n-ride station that provide the community with visions to promote smart growth and a sustainable future.
Keywords: Lee's Summit; Ridership; Transit dependency; Suburban transit; Sustainable growth; Landscape Architecture (0390); Land Use Planning (0536)